2014
DOI: 10.1080/10503307.2014.901572
|View full text |Cite
|
Sign up to set email alerts
|

The impact of early empathy on alliance building, emotional processing, and outcome during experiential treatment of depression

Abstract: Empirical support was provided for the theorized relationships in experiential theory amongst the variables examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 59 publications
4
46
0
Order By: Relevance
“…Additionally, therapists were more likely to use higher levels common factors techniques with patients with whom they established a stronger alliance early in treatment. This finding supports earlier studies which have shown a relation between supportive or rapport building techniques and better alliance (Ackerman & Hilsenroth, ; Karver et al, ; Malin & Pos, ). Our results perhaps suggest that techniques shared by all treatment modalities (rather than those that are theory driven) have a stronger impact on the development of alliance (Messer & Wampold, ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, therapists were more likely to use higher levels common factors techniques with patients with whom they established a stronger alliance early in treatment. This finding supports earlier studies which have shown a relation between supportive or rapport building techniques and better alliance (Ackerman & Hilsenroth, ; Karver et al, ; Malin & Pos, ). Our results perhaps suggest that techniques shared by all treatment modalities (rather than those that are theory driven) have a stronger impact on the development of alliance (Messer & Wampold, ).…”
Section: Discussionsupporting
confidence: 92%
“…To the best of our knowledge, only two small studies have found a positive relation between therapist use of common factors techniques earlier in treatment and a stronger patient‐reported alliance later in treatment among depressed adolescents (Karver et al, ) and adults (Malin & Pos, ).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Malin and Pos () investigated the links between empathic communication (as rated by observers of first session), alliance quality (as reported by clients after first session), and depressive symptom reduction (as reported by clients) in short‐term experiential therapy. Clients in this study were 30 depressed clients with relatively high or low alliance scores who were drawn from a larger client pool ( n = 74).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to Malin and Pos's () study, we utilized client ratings of empathy because we deemed the experience of empathy (Barrett‐Lennard, ) to be more relevant in this context than therapist‐rated attunement (Rogers, ) or observer‐rated communication (Rogers, ). In particular, we surmised that the effect of attunement/communication might be contingent on the client's perception of that attunement/communication; if a client is unaware of an empathic communication, then we would expect that she would be no more receptive (Wong, ) to therapeutic goals/tasks .…”
Section: Introductionmentioning
confidence: 99%